Determinan pertumbuhan laba industri otomotif di Indonesia (studi empiris pada PT. Astra Internasional Tbk.) - Herlin, Faradilla; Veronica, Deka; Rosita, Ratih; Neldawaty, Rika (Jurnal Paradigma Ekonomika, 2022)
The company's financial performance will be a benchmark for investors to invest. During the COVID-19 pandemic, the automotive industry experienced a decline in economic performance, mainly profits from the company. The main focus of this research is to find out what factors influence profit growth in the automotive industry (a case study at PT. Astra Internasional Tbk) with the indicators used, namely the ratio of ROA, ROE, current ratio, and DAR. This study uses secondary data obtained from the company's annual report for 2010 to 2020. The results show that the company's profit growth is influenced by financial performance, namely profitability, liquidity, and solvency. The higher the company's profitability performance, the profit will increase while the liquidity and solvency variables become variables that have a negative effect on the company's profit growth.